Pengaruh E-Planning dan E-Budgeting Terhadap Sistem Akuntabilitas Kinerja Pada Organisasi Perangkat Daerah (OPD) Kota Palembang - Miranda Yulianti; Sandrayati Sandrayati; Kurnia Widya Oktarini (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
E-government is the use of information and communication technology in governance to improve effectiveness, efficiency, and accountability. This study aims to determine the effect of E-Planning and E-Budgeting on the performance accountability system in Regional Apparatus Organizations (OPD) in Palembang City. The sample used was the LAKIP report from 27 Regional Apparatus Organizations in Palembang City for the period 2022-2024. The research method used was quantitative with secondary data collection from the official website of the Palembang City government. The research object was the OPD of Palembang City. The results showed that E-Planning negatively affected performance accountability, while E-Budgeting did not. Simultaneously, the two independent variables, namely E-Planning and E-Budgeting, together significantly influenced accountability. The implications of this study emphasize the importance of utilizing information technology in increasing transparency, efficiency, and public participation in regional governance.